PENGARUH GLOBALISASI PADA RUANG SEBUAH KASUS DARI MASA LALU - Mrs. Suastiwi (Ars: Jurnal Seni Rupa dan Desain, 2009)
Globalization is a certainty that changes the world. In Indonesia, the process of globalization was initiated at the early stage of the Christian Calendar that was marked by the incoming of Indian, Chinese, Islamic, and Western culture successively. This article will discuss a case of globalization on space of Rumah Gedhong in Kampung Kauman Yogyakarta. It aimed at seeking the relationship between culture and the space of human activity and investigating how the space changes according to the transformation on the lifestyle and the values or in a bigger scale, the culture of the people.Keywords: globalization, culture, activity, space